2019
DOI: 10.1017/s1478951519000154
|View full text |Cite
|
Sign up to set email alerts
|

What do family caregivers know about palliative care? Results from a national survey

Abstract: Objective. Despite their key role in caring for individuals with serious, chronic illness, there have been no national studies examining family caregiver awareness and perceptions of palliative care. Hence, our objectives were to ascertain level of knowledge of palliative care among U.S. family caregivers and describe demographic variation in awareness and perceptions of palliative care. Method. Using the 2018 National Cancer Institute Health Information National Trends Survey, we identified unpaid family ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 35 publications
2
39
0
2
Order By: Relevance
“…[23] The finding that all of the respondents were literate and the majority of the study participants were at least graduates may have had a bearing on the levels of awareness and knowledge about PCA study in the US found the same association. [21] In this sample of care giver's, half of them were close relatives of the patient, like wife, husband, sister or brother divided almost equally, while the remaining were nurses, nursing attendants or distant relatives. This matches findings in international studies where close family members take on the role of care giver when a spouse, parent, or child or a relative falls ill. [24,25] In the Pakistani setting the care giver is often a relative and often considers the opportunity to be an honor and a privilege.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…[23] The finding that all of the respondents were literate and the majority of the study participants were at least graduates may have had a bearing on the levels of awareness and knowledge about PCA study in the US found the same association. [21] In this sample of care giver's, half of them were close relatives of the patient, like wife, husband, sister or brother divided almost equally, while the remaining were nurses, nursing attendants or distant relatives. This matches findings in international studies where close family members take on the role of care giver when a spouse, parent, or child or a relative falls ill. [24,25] In the Pakistani setting the care giver is often a relative and often considers the opportunity to be an honor and a privilege.…”
Section: Discussionmentioning
confidence: 88%
“…It is noteworthy that these numbers are comparable with a large study done in the US in 2019, because the same percentage of caregiver's (55%), had never heard of palliative care, whereas 19.2 % knew what palliative care was and believed they would be able to explain it to someone else. [21,26] A study done on the general population in the US, found misperceptions and negative attitudes towards palliative care even though palliative care is more widely available there. [27] The PC approach stresses that the diagnosis of an incurable disease does not mean that nothing more can be done for the patient, on the contrary, a great deal can still be done to decrease and control physical and psychological symptoms, social issues and spiritual suffering of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a clear role for palliative care throughout DLB and hospice care at the EOL, many participants voiced lack of knowledge regarding hospice and lack of education and assistance from their physicians. This may reflect a more general lack of public and caregiver knowledge regarding palliative care [31]. Lack of family and physician knowledge are known barriers to hospice care in dementia [20] and caregivers report difficulty accessing hospice for family members with dementia [32].…”
Section: Discussionmentioning
confidence: 99%